2012
DOI: 10.1037/a0024617
|View full text |Cite
|
Sign up to set email alerts
|

Should social savvy equal good spatial skills? The interaction of social skills with spatial perspective taking.

Abstract: Real-world perspective-taking problems frequently involve interactions among individuals, suggesting a potential social element to this seemingly spatial problem. Previous studies have suggested that the agency of the target in a perspective-taking task might influence reasoning. This hypothesis is tested directly by manipulating whether one takes the perspective of a potential agent or an object. The results were striking: Even though no overall differences in performance were observed with and without agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 25 publications
9
74
5
2
Order By: Relevance
“…For instance, visuo-spatial perspective-taking and social skills, a measure of general empathic functioning (exemplary item: "I enjoy social occasions"; cf. Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001), are positively correlated (e.g., Brunyé et al, 2012;Shelton, Clements-Stephens, Lam, Pak, & Murray, 2012;Thakkar, Brugger, & Park, 2009). Furthermore, autism spectrum disorder-an extreme case of social and empathic dysfunction-has been associated with deficits in visuo-spatial perspectivetaking (Hamilton, Brindley, & Frith, 2009).…”
Section: Sascha Topolinski University Of Colognementioning
confidence: 96%
“…For instance, visuo-spatial perspective-taking and social skills, a measure of general empathic functioning (exemplary item: "I enjoy social occasions"; cf. Baron-Cohen, Wheelwright, Skinner, Martin, & Clubley, 2001), are positively correlated (e.g., Brunyé et al, 2012;Shelton, Clements-Stephens, Lam, Pak, & Murray, 2012;Thakkar, Brugger, & Park, 2009). Furthermore, autism spectrum disorder-an extreme case of social and empathic dysfunction-has been associated with deficits in visuo-spatial perspectivetaking (Hamilton, Brindley, & Frith, 2009).…”
Section: Sascha Topolinski University Of Colognementioning
confidence: 96%
“…However, it is still unclear as to whether such a rudimentary system is inherently dedicated to process specifically social information or whether it is more domain general in nature. In other words, it has yet to be clarified whether this is a generic system for processing potentially conflicting information without specific reference to the domain (Egner, Etkin, Gale, & Hirsch, 2008;Zaki, Hennigan, Weber, & Ochsner, 2010) or whether it is selective for social information such as that likely to involve a social agent (Kovács et al, 2010;Shelton, Clements-Stephens, Lam, Pak, & Murray, 2011). Domain-general accounts for belief and perspective understanding are plausible (Perner, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first systematic investigation of the influence of differing degrees of social relevance. To do this we manipulated the presence or otherwise of a social agent (Böckler, Knoblich, & Sebanz, 2012;Kovács et al, 2010;Shelton et al, 2011). Participants were presented with either a social cue (avatar; , a semisocial cue (arrow, which possesses both symbolic and social characteristics; Kingstone, Tipper, Ristic, & Ngan, 2004;Ristic, Friesen, & Kingstone, 2002; see also Zwickel, 2009), or a non-social cue (a dualcoloured block).…”
Section: Introductionmentioning
confidence: 99%
“…The latter, termed visual-spatial perspective taking (VSPT), has traditionally been considered a form of spatial problem solving. However, over the course of the last decade, there has been a growing body of research supporting a relationship between one's social abilities and the ease with which they are able to engage in this more visually driven form of perspective taking (Brunyé et al, 2012; Kessler and Wang, 2012; Shelton et al, 2012), highlighting the role of VSPT for everyday social interactions. Impairment on tasks that require adopting another's perspective—be it to judge if an object is visible from another viewpoint (Level 1 VSPT) or to represent what a spatial layout might look like from another viewpoint (Level 2 VSPT)—is a hallmark feature of Autism Spectrum Disorders (ASD; Baron-Cohen, 1992; Best et al, 2008).…”
mentioning
confidence: 99%
“…Impairment on tasks that require adopting another's perspective—be it to judge if an object is visible from another viewpoint (Level 1 VSPT) or to represent what a spatial layout might look like from another viewpoint (Level 2 VSPT)—is a hallmark feature of Autism Spectrum Disorders (ASD; Baron-Cohen, 1992; Best et al, 2008). A vast majority of the research examining this relationship between social and VSPT abilities tends to come in two forms: either investigation of how/when VSPT abilities are impaired or preserved in individuals with ASD due to their known deficits in social skills (Hobson, 1984; David et al, 2006; Hamilton et al, 2009; Gould et al, 2011; Zwickel et al, 2011; Schilbach et al, 2012) or investigations of the natural variability that is observed in more typically-developing populations (Brunyé et al, 2012; Shelton et al, 2012). …”
mentioning
confidence: 99%